PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI DALAM PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 31 PADANG - Reza Mariska; Nursaid (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aims to analyze the effect of Project Based Learning (PBL) model assisted by serial picture media on news text writing skills of seventh grade students of SMP Negeri 31 Padang. Specifically, this study describes the skills of writing news texts before and after the application of the PBL model and tests its effectiveness in improving students' abilities. The method used in this research is experimental with one group pretest-posttest design. The research sample consisted of 32 students selected through purposive sampling technique. The research instrument was a news text writing skill test given before and after treatment. The results showed that there was a significant improvement in students' writing skills after the application of the PBL model assisted by serialized picture media. Before the treatment, the majority of students were in the moderate category in news text writing skills, while after the treatment, the results increased to the good category. The use of serial images proved to help students in organizing ideas and understanding the structure of news texts better. Thus, the PBL model assisted by serialized picture media can be used as an effective learning strategy in improving students' writing skills, especially in news texts.